Bills of lading - Aikens, Richard; Lord, Richard 1959-; Bools, Michael D. (Lloyd's shipping law library, 2016)
Bills of Lading form an essential part of the carriage of goods by sea and international trade. Their multi-functional nature, together with the large volume of case law and regulation, make the law in this field as complex is it is commercially vital. This bestselling book provides a detailed analysis of the law and practice applicable to bills of lading before, during and after shipment, helping today's busy practitioner to quickly and easily find the information they need